Prospects for optical detections from binary neutron star mergers with the next-generation multi-messenger observatories - Loffredo, Eleonora; Hazra, N.; Dupletsa, U.; Branchesi, M.; Ronchini, S.; Santoliquido, F.; Perego, A.; Banerjee, B.; Bisero, S.; Ricigliano, G.; Vergani, S.; Andreoni, I.; et al. (Astronomy and astrophysics, 2025)
Context. Next-generation gravitational wave (GW) observatories, such as the Einstein Telescope (ET) and Cosmic Explorer, will observe binary neutron star (BNS) mergers across cosmic history, providing precise parameter estimates for the closest ones. Innovative wide-ﬁeld observatories, such as the Vera Rubin Observatory, will quickly cover large portions of the sky with unprecedented sensitivity to detect faint transients.
Gesehen am 27.10.2025